Dinamika Relasi Gender, Fakultas dan Lembaga di Lingkungan Universitas Malikussaleh: Catatan Awal - Jamaluddin Jamaluddin; Apridar; Nanda Amali; Al Chaidar (SIASAT, 2019)
This article argues that in the context of Malikussaleh University, the position of women is still often confronted with the position of men. The position of women is always associated with the domestic environment related to matters of family and household. While the position of men is often associated with the public environment related to matters outside the home. In a social structure, the position of such women is difficult to balance the position of men. Women who want to take part in the public sphere, it is still difficult to escape from their responsibilities in the domestic sphere. Women in this case are powerless to avoid the double burden because their duties as caretakers are a general cultural perception. Cultural control seems to be more stringent to women than men